Diagnóstico de la capacidad de movilidad peatonal en los andenes de la carrera 8ª entre calle 15 y 16 de la ciudad de Pereira departamento de Risaralda (2022)
The development of this degree project is based on the elaboration of a diagnosis of pedestrian mobility in the 8th race between Calle 15 and 16 in the city of Pereira - Risaralda, an area that is known to be very busy, located in the corridor between the Bolívar and La Libertad parks, an area known for its commercial development and high vehicular flow.